2018
DOI: 10.1371/journal.pone.0199549
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of normative hand movements during two functional upper limb tasks

Abstract: BackgroundDexterous hand function is crucial for completing activities of daily living (ADLs), which typically require precise hand-object interactions. Kinematic analyses of hand trajectory, hand velocity, and grip aperture provide valuable mechanistic insights into task performance, but there is a need for standardized tasks representative of ADLs that are amenable to motion capture and show consistent performance in non-disabled individuals. Our objective was to develop two standardized functional upper lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
133
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 53 publications
(134 citation statements)
references
References 49 publications
1
133
0
Order By: Relevance
“…Data from two participants were removed due to problems arising from software issues. The characteristics of the 20 participants from the original study [7]–[9] and the 20 participants in the repeated study are detailed in Error! Reference source not found.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Data from two participants were removed due to problems arising from software issues. The characteristics of the 20 participants from the original study [7]–[9] and the 20 participants in the repeated study are detailed in Error! Reference source not found.…”
Section: Methodsmentioning
confidence: 99%
“…Various functional assessments are used to gauge the functional impact of upper limb impairment and to monitor rehabilitative progress thereafter [5], [6]. However, such assessments often do not precisely quantify hand and joint movements, grip adjustments [7], [8], or hand-eye interaction, which is recognized as an important behaviour during grasp control [9], [10]. Quantitative measurement of visuomotor behaviour collected during the execution of functional tasks can enhance the understanding of these movement features.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations